Sports marketing a practical approach - DeGaris, Larry (London Routledge, 2015)
"Any sports marketing student or prospective sports marketer has to understand in detail genuine industry trends and be able to recognise solutions to real-world scenarios. Sports Marketing: A Practical Approach is the first textbook to offer a comprehensive, engaging and practice-focused bridge between academic theory and real-life, industry-based research and practice. Defining the primary role of the sports marketer as revenue generation, the book is structured around the three main channels through which this can be achieved -- ticket sales, media and sponsorship -- and explores key topics such as: Sports markets and business markets (b2b) Fan development Brand management Media audiences, rights and revenue Live sports events Sponsorship Merchandise and retail Integrating real industry-generated research into every chapter, the book also includes profiles of leading industry executives and guidance for developing and preparing for a career in sports marketing. It goes further than any other sports marketing textbook in surveying the international sports market, including international cases and detailed profiles of international consumer and business markets throughout. A companion website offers a testbank, slides, web links and other useful features for teaching and learning. No other textbook offers such a relevant, practice-focused overview of contemporary sports marketing. It is the ideal companion to any sports marketing course"--Provided by publisher.
1. A Practical Approach to Sports Marketing 2. Sports Markets 3. Fan Development 4.Brand Management 5. Gate Revenue Marketing Mix 6. Consumer Ticket Sales 7. Corporate Ticket Sales 8. Sports Media 9. Sports Media Audiences 10. Sports Publicity 11. Sports Advertising Sales 12. Sponsorship: What It Is and How It Works 13. Sponsorship Goals and Strategies 14. Sponsorship Activation 15. Sponsorship Measurement 16. Sponsorship Sales
Includes bibliographical references and index.
Keywords: Sports -- Marketing; Sports -- Economic aspects